Jāmiʿ al-aḥkām fī fiqh al-islām - Amīr ʿAlī Malīḥābādī, Saiyid
Urdu translation of Islamic law (fiqh), both Sunni and Shia viewpoints, on: (v. 1) personal matters like inheritance, marriage and divorce; (v. 2) the issues of hibah (gifts) and vaqf (land-grants to institutions)